Belowground Carbon Efficiency for Nitrogen and Phosphorus Acquisition Varies Between Lolium perenne and Trifolium repens and Depends on Phosphorus Fertilization - Lu, Jiayu; Yang, Jinfeng; Keitel, Claudia; Yin, Liming; Wang, Peng; Cheng, Weixin; Dijkstra, Feike A. (Frontiers in Plant Science, 2022)
Photosynthetically derived carbon (C) is allocated belowground allowing plants to obtain nutrients. However, little is known about the amount of nutrients acquired relative to C allocated belowground, referred as C efficiency for nutrient acquisition (CENA). Here we examined how C efficiency for nitrogen (N) and phosphorus (P) acquisition varied between ryegrass (Lolium perenne) and clover (Trifolium repens) with and without P fertilization. A continuous 13C-labeling method was applied to track belowground C allocation. Both species allocated nearly half of belowground C to rhizosphere respiration (49%), followed by root biomass (37%) and rhizodeposition (14%). With regards to N and P, CENA was higher for clover than for ryegrass, which remained higher after accounting for relatively low C costs associated with biological N2 fixation. Phosphorus fertilization increased the C efficiency for P acquisition, but decreased the C efficiency for N acquisition. A higher CENA for N and P in clover may be attributed to the greater rhizosphere priming on soil organic matter decomposition. Increased P availability with P fertilization could induce lower C allocation for P uptake, but exacerbate soil N limitation thereby making N uptake less C efficient. Overall, our study revealed that species-specific belowground C allocation and efficiency for nutrient uptake depend on which nutrient is limited.